Comparative constitutional law - Basu, Durga Das. (Gurgaon, 2014)
Dr Durga Das Basu's Comparative Constitutional Law has its beginning from the law lectures in B.H.U. A work of good research has been immensely improved by the author. Lucid readable and of great value to students of politics, law and to the legal profession. The topics have been detailed in a manner that makes it most intelligible and fluent. The first edition incorporated precedents till 1983. This revised edition has brought in precedents till the early part of 2014. The basic chapters remaining the same, substantial value has been added keeping in view the latest developments on the subject over these years.
Keywords: Constitutional law